Supply chain attack on Kaseya compromises hundreds of firms. Issue 7 (July 2021) - Unknown
Abstract : The REvil ransomware group has exploited zero-day flaws in Kaseya's VSA IT management and remote monitoring solution to infect a large number of organisations with ransomware. When the dust settles, this is likely to be seen as the largest-ever ransomware attack.